2011
DOI: 10.1186/1471-2164-12-161
|View full text |Cite
|
Sign up to set email alerts
|

Gene discovery in EST sequences from the wheat leaf rust fungus Puccinia triticina sexual spores, asexual spores and haustoria, compared to other rust and corn smut fungi

Abstract: BackgroundRust fungi are biotrophic basidiomycete plant pathogens that cause major diseases on plants and trees world-wide, affecting agriculture and forestry. Their biotrophic nature precludes many established molecular genetic manipulations and lines of research. The generation of genomic resources for these microbes is leading to novel insights into biology such as interactions with the hosts and guiding directions for breakthrough research in plant pathology.ResultsTo support gene discovery and gene model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 57 publications
(78 reference statements)
7
68
0
Order By: Relevance
“…Previously, haustorial transcriptomes of obligate biotrophic rust fungi have been shown to contain many transcripts involved in metabolism and protein synthesis as well as virulence (Catanzariti et al, 2006;Hahn and Mendgen, 1997;Xu et al, 2011;Yin et al, 2009). This is in line with our results, as we identified elements of gene expression and protein turnover to be the most abundant transcripts (Fig.…”
Section: Transcripts Of Primary Metabolism Dominate the Haustorial Trsupporting
confidence: 94%
See 1 more Smart Citation
“…Previously, haustorial transcriptomes of obligate biotrophic rust fungi have been shown to contain many transcripts involved in metabolism and protein synthesis as well as virulence (Catanzariti et al, 2006;Hahn and Mendgen, 1997;Xu et al, 2011;Yin et al, 2009). This is in line with our results, as we identified elements of gene expression and protein turnover to be the most abundant transcripts (Fig.…”
Section: Transcripts Of Primary Metabolism Dominate the Haustorial Trsupporting
confidence: 94%
“…A comparatively low number of genes with homologs is also within the range of reports from rust (Puccinia striiformis f.sp. tritici) haustorial cDNA libraries (Xu et al, 2011;Yin et al, 2009). The genome of Bgh contains 5854 curated genes, a low number in comparison to other fungi (Schmidt and Panstruga, 2011;Spanu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This large genome size is in part explained by transcriptome analyses that showed unique genes are expressed by different stages of the life cycle (Hacquard et al 2013;Xu et al 2011). Microcyclic rust fungi can lose their aecial and uredinial stages in conditions favourable for continuous growth and reproduction (Ono 2002); the unique genes associated with these stages may remain in the genome, but are not expressed.…”
Section: Discussionmentioning
confidence: 99%
“…A larger number of genes specifically expressed in telia were found, most of which encode unknown functions. Similarly, a large number of specific ESTs with unknown functions were identified in P. triticina teliospores (Xu et al, 2011) highlighting that the biological processes associated with this type of rust spores remain mostly uncharacterized. In M. larici-populina, telia and uredinia have the most similar expression profiles when compared to fungal hyphae undergoing biotrophic growth in poplar leaves, indicating shared components in the genetic programs ongoing in these spore-forming structures.…”
Section: Genome Oligoarray-based Transcriptomicsmentioning
confidence: 97%
“…These gene expression studies particularly showed that the haustorium is a crucial structure both for nutrients uptake (Mendgen & Hahn, 2002;Voegele, Hahn, & Mendgen, 2009;Voegele, Struck, Hahn, & Mendgen, 2001) and effector release (Catanzariti, Dodds, Lawrence, Ayliffe, & Ellis, 2006;Hahn & Mendgen, 1997;Joly, Feau, Tanguay, & Hamelin, 2010;Link & Voegele, 2008). A few studies explored other stages of the rust fungi biology, providing insights into relevant functions expressed at various developmental steps of the rust life cycle (Warren & Covert, 2004;Xu et al, 2011). Most expression studies were focused on resting rust uredospores collected outside the host plant and during in planta biotrophic growth by directly isolating RNA from infected host tissues.…”
Section: Rust Transcriptomicsmentioning
confidence: 98%